2007
DOI: 10.1099/mic.0.2007/006692-0
|View full text |Cite
|
Sign up to set email alerts
|

Intact-cell MALDI-TOF mass spectrometry analysis of peptaibol formation by the genus Trichoderma/Hypocrea: can molecular phylogeny of species predict peptaibol structures?

Abstract: Peptaibols are characteristic linear a-aminoisobutyrate-containing peptides produced by certain Ascomycetes, especially of the genus Hypocrea/Trichoderma [Hypocrea and Trichoderma are the names for the teleo-and anamorph forms of the same taxon; where known to occur in nature, the teleomorph is used to name the species. To aid the inexperienced reader, both names (the less well known one in parentheses) are given at the first mention of each species.] Here we have investigated whether phylogenetic relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
61
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 91 publications
(82 reference statements)
0
61
0
Order By: Relevance
“…Depending upon the strain, Trichoderma spp. produce either a 11-residue peptaibol or a 14-residue peptaibol, or both (19). Although, we initially reported that the deletion of Tex1 resulted in the loss of all three (18, 14, and 11-residue) peptaibols, it was subsequently confirmed by us and another group that Tex1 codes for only the 18-residue peptaibol (26,33,34).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 70%
See 4 more Smart Citations
“…Depending upon the strain, Trichoderma spp. produce either a 11-residue peptaibol or a 14-residue peptaibol, or both (19). Although, we initially reported that the deletion of Tex1 resulted in the loss of all three (18, 14, and 11-residue) peptaibols, it was subsequently confirmed by us and another group that Tex1 codes for only the 18-residue peptaibol (26,33,34).…”
Section: Journal Of Biological Chemistrymentioning
confidence: 70%
“…As already suggested, both types of peptaibols could originate from a single peptide synthetase. Based on the available sequence comparison of 11-and 14-residue peptaibols, Neuhof et al (19) predicted that SF4 11-(group 6) and 14-residue (groups 8, 9, and 11) compounds could be produced by a single peptaibol synthetase by deletion of modules 3-5 (Leu3-Pro4-Aib5). Nevertheless, taking into account the alignments of the sequences, it seems that in Gv29-8, 11-residue peptaibols could be derived from 14-residue peptaibols by internal deletion of the residues in positions 4, 5, and 6 or could be synthesized by an enzyme that is lacking the modules for incorporation of residues 4, 5, and 6.…”
Section: Journal Of Biological Chemistrymentioning
confidence: 99%
See 3 more Smart Citations